Brief Report: HCV Universal Test-and-Treat With Direct Acting Antivirals for Prisoners With or Without HIV. (15th December 2021) - Supanan, Ruamthip; Han, Win Min; Harnpariphan, Weerakit; Ueaphongsukkit, Thornthun; Ubolyam, Sasiwimol; Sophonphan, Jiratchaya; Tangkijvanich, Pisit; Thanprasertsuk, Sombat; Avihingsanon, Anchalee
Abstract : Background: This study investigated the sustained virologic responses (SVRs) among prisoners with hepatitis C virus (HCV) using universal test-and-treat approach by prison health care workers in a central male prison in Thailand. Methods: A universal HCV screening was conducted in a maximum-security central prison (Klong Prem Central Prison) in Thailand. HCV RNA–confirmed prisoners were treated with generic sofosbuvir/velpatasvir by prison health care workers, regardless of their HCV genotypes and duration of prison sentences. We evaluated the SVR rates at 12 weeks after completing direct acting antivirals (DAA) treatment. Results: A total of 68 prisoners with detectable HCV RNA received DAA treatment. The median age and duration of prison sentences were 44 years (interquartile range, 41–53) and 25 (interquartile range, 19–33) years, respectively. Twenty-five percentage of the participants was coinfected with HIV, and 6% of the participants was coinfected with hepatitis B virus. Among all prisoners who received DAA treatment, 20 (29%) had genotype (GT)-1a, 3 (4%) had GT-1b, 22 (32%) had GT-3a, 3 (4%) had GT-3b, and 7 (10%) had GT-6. Overall, improvements in liver biomarkers were seen after HCV treatment, and SVR was achieved in 97% of the participants with per-protocol analysis and in 90% of the participants with intention-to-treat analysis. Conclusions: HCV treatment using DAA among prisoners through universal test-and-treat approach led by prison health care workers is highly effective and safe, and such model can potentially help to facilitate the goals of HCV microelimination among prisoners in Thailand.